MORAL VALUES IN ATLANTICS MOVIE (2019) DIRECTED BY MATI DIOP DEMANGEL - Hidayati, Lia Nurul; Arifin, Adip; Harida, Ratri (STKIP PGRI Ponorogo Press, 2022)
This research is aimed at analyzing the moral values in Atlantics movie. Moral values are values related to good and bad human actions or behavior. Generally, moral is used to assess someone’s attitude and behavior. The method used in this research was descriptive qualitative. The data are collected by observing the Atlantics movie and then identifying the words, actions (scenes) and behavior of the characters that presenting the moral values. The data then analyzed by employing the interactive model of analysis, by Miles and Hubberman (1994) consisted of; reduction, display and verification or drawing conclusion. The results of the analysis showed that there were five moral values found in Atlantics film, as follows; courage, love and affection, honesty, self-confidence and kindness. To sum up, honesty was the dominant moral value that appeared in the film. From this research, it can be concluded that Atlantics film provided moral messages about the meaning and importance of moral values for human life.